Pengaruh Penerapan e-SPT Terhadap Kepatuhan Wajib Pajak Badan Dalam Melaporkan SPT (Studi Kasus Pada KPP Madya Malang) - Sari, Novi Purnama (Jurnal Mahasiswa Perpajakan, 2014)
Direktorat Jenderal Pajak (DJP) has sought to reform the administrative system of modern taxation. One of the implementations is e-SPT in order to provide ease of service for taxpayers in their tax reporting. Implementation of e-SPT system is expected to increase the level of taxpayer compliance in reporting SPT. The purpose of this study was to determine. The purpose of this study was to determine the effect of the implementation of e-SPT consisting of usefulness, ease of use and facilitating conditions toward corporate taxpayer compliance to report e-SPT simultaneously and partially as well as the most dominant influence. This research was conducted in March 2014 in KPP Madya Malang, by spreading questionnaires to corporate taxpayers who use e-SPT system. Sample was taken by purposive sampling method and there are 93 respondents. The answer is measured with a Likert scale. The data obtained were analyzed using multiple regression, t test and F test. Results of analysis showed that variable usefulness, ease of use and facilitating conditions simultaneously and partially have a significant effect toward corporate taxpayer compliance in reporting e-SPT. Keywords: e-SPT Application, Usefulness, Ease of Use And Facilitating Conditions And CorporateÂ  Taxpayer Compliance In Reporting SPT